Design and development of a laser interferometer for magnet alignment and phase error analysis in an undulator. (April 2020) - Mishra, G.; Khan, Saif Mohd; Gehlot, Mona
Highlights: Magnet misalignments in undulator is a source of large field integral and phase error. Can be improved by a laser interferometer. The laser interferometer moves along the length of the undulator. Monitors the misalignments through fringe shifts. Magnet alignment can be improved by tightening or loosening the magnet clamps. Abstract: In this paper we discuss design and development of a laser interferometer for undulator measurement application. The vertical misalignment of the magnets in the undulator results in non uniformity in the undulator gap and leads to non uniform magnetic field along the length of the undulator. The non uniformity in the magnetic field gives rise to trajectory wander and phase error. The trajectory wander and the phase error are the source of reduction in spontaneous emission and free electron laser gain. The effect is more severe for free electron lasers operating at higher harmonics. It is demonstrated that the laser interferometer can be used effectively to measure and correct the magnet alignments of the undulator.